KOMPILASI HUKUM ISLAM: KONSEP PERSETUJUAN WANITA DALAM PERNIKAHAN PANDANGAN IBN QAYYIM AL-JAWZIYAH DAN KOMPILASI HUKUM ISLA - superadmin superadmin (IAIC (Institut Agama Islam Cirebon), 2020)
Marriage is a high respect and appreciation given to humans from Allah SWTamong other creatures. In the Compilation of Islamic Law, Chapter II article 2 states: